Peran Guru BK Dalam Mengimplementasikan Program Layanan Bimbingan dan Konseling Di SMA Negeri 2 Luwuk - Arnila; LAMBAUSE, HASAN (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Tompotika Luwuk, 2025)
This study is a qualitative study that aims to determine the Role of Guidance and Counseling Teachers in Implementing Guidance and Counseling Service Programs at SMA Negeri 2 Luwuk. The subjects of this study were 6 people consisting of 1 Principal, 1 Guidance and Counseling Teacher, and 4 students. Data collection techniques were Observation, Interviews, and Documentation. Based on the research that has been conducted on students regarding the Role of BK Teachers in Implementing Guidance and Counseling Service Programs at SMA Negeri 2 Luwuk, researchers can conclude that the Role of BK Teachers in Implementing Guidance and Counseling Service Programs at SMA Negeri 2 Luwuk is good, namely the role of BK teachers when providing services to students who have problems, and the implementation of BK service programs carried out by BK teachers, namely service programs and there are 4 services, namely personal, social, learning and career services and supporting facilities and infrastructure in the guidance and counseling service program. Keywords: Role of Teachers, Implementation, Service Programs.